2008
DOI: 10.1370/afm.842
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Brief Diabetes Distress Screening Instrument

Abstract: PURPOSE Previous research has documented that diabetes distress, defi ned as patient concerns about disease management, support, emotional burden, and access to care, is an important condition distinct from depression. We wanted to develop a brief diabetes distress screen instrument for use in clinical settings. METHODSWe assessed 496 community-based patients with type 2 diabetes on the previously validated, 17-item Diabetes Distress Scale (DDS17) and 6 biobehavioral measures: glycated hemoglobin (HbA 1c ); no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
346
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(371 citation statements)
references
References 14 publications
5
346
1
7
Order By: Relevance
“…Ten items loaded above 0.50, all of which were from the Diabetesrelated Negative Emotions subscale (items 3,6,7,8,9,10,12,16,19,20). We removed three items rated on average by respondents as less than a 'minor problem' (items 8, 10, 20) and the remaining seven items were subjected to a reliability analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten items loaded above 0.50, all of which were from the Diabetesrelated Negative Emotions subscale (items 3,6,7,8,9,10,12,16,19,20). We removed three items rated on average by respondents as less than a 'minor problem' (items 8, 10, 20) and the remaining seven items were subjected to a reliability analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a two-item screening version of the Diabetes Distress Scale (DDS) was validated and showed good sensitivity (95%) and specificity (85%) [8]. However, as the PAID remains a more widely used instrument, we aimed to develop a five-item short form for routine clinical and research use and a single-item measure that may be used as a rapid screen for diabetes-related emotional distress.…”
mentioning
confidence: 99%
“…Compared with the general population, clinical depression and anxiety occur about twice as often among persons with both type 1 and type 2 diabetes [3][4][5][6], and the risk of eating disorders is also increased [7]. Furthermore, a large number of persons with diabetes suffer from diabetes distress, the semi-chronic stress condition resulting from the strains of living with diabetes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A review of web-based interventions for comorbid depression and chronic illness showed that participants valued psychoeducation with illness-specific examples [55]. Furthermore, because of the positive results in face to-face psychotherapy efficacy when there is inclusion of diabetes self-management interventions [18,19], and the close association between diabetes distress and depression [2], we can think that the inclusion of diabetes-specific topics is desirable.…”
Section: Diabetic-specific Topics Vs Generic Depression Interventionmentioning
confidence: 99%
“…There is substantial evidence that depression among individuals with diabetes is associated with poorer diabetes outcomes [1] and higher levels of diabetes distress (emotional burdens, stresses and worries associated with diabetes) [2]. When depressed, patients with diabetes show a higher frequency of hypoglycemia, higher levels of glycosylated hemoglobin (HbA1c) and their risk of developing diabetes-related complications increases [3][4][5].…”
Section: Introductionmentioning
confidence: 99%